2008
DOI: 10.1159/000138887
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial germ cell tumors: association with Klinefelter syndrome and sex chromosome aneuploidies

Abstract: Intracranial germ cell tumors (ICGCTs) occur mainly in male children and adolescents. Polyploidy of the X chromosome and X hypomethylation have been suggested as mechanisms of malignant transformation independently of the histological tumor type. On the other hand, several reports associate these tumors with Klinefelter’s syndrome (KS). Recent reports indicate that KS patients have an increased relative risk for development of malignant mediastinal germ cell tumors and also around 8% of male patients with prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…Germinomas have been associated with specific hereditable syndromes. For example, there is an increased increase incidence of germinoma in Klinefelter, Noonan and Down's [7] syndromes [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Germinomas have been associated with specific hereditable syndromes. For example, there is an increased increase incidence of germinoma in Klinefelter, Noonan and Down's [7] syndromes [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the sex chromosomal aneuploidy in these men leads to early apoptosis of germ cells due to the inability for proper chromosome pairing during meiosis [Wikströ m et al, 2004]. However, men with Klinefelter syndrome have a higher risk of developing a highly aggressive GCC of the mediastinum and brain [Bokemeyer et al, 2002;Völkl et al, 2006;Queipo et al, 2008].…”
Section: Klinefelter As a Separate Groupmentioning
confidence: 99%
“…However, the frequency of KS among patients with intracranial GCT is not well established. Queipo et al found in a small series of patients with intracranial GCTs (n = 13) that 15% of their cohort had a non-mosaic 47, XXY karyotype [24]. As such, a karyotype should be considered in a male with an intracranial GCT who has features of KS.…”
Section: Intracranial Germ Cell Tumorsmentioning
confidence: 99%
“…Patients who received radiation doses of > 22 Gy to the hypothalamus/pituitary have a decreased rate of pregnancy [73]. Even lower doses of radiation (18)(19)(20)(21)(22)(23)(24) have been associated with decreased fertility in cancer survivors compared to sibling controls [74,75].…”
Section: Gonadal Failure In Girlsmentioning
confidence: 99%